The lysolipid transporter Mfsd2a regulates lipogenesis in the developing brain - Chan, Jia Pei; Wong, Bernice H.; Chin, Cheen Fei; Galam, Dwight L. A.; Foo, Juat Chin; Wong, Loo Chin; Ghosh, Sujoy; Wenk, Markus R.; Cazenave-Gassiot, Amaury; Silver, David L. (PLoS biology, 2018)
Brain development requires a massive increase in brain lipogenesis and accretion of the essential omega-3 fatty acid docosahexaenoic acid (DHA). Brain acquisition of DHA is primarily mediated by the transporter Major Facilitator Superfamily Domain containing 2a (Mfsd2a) expressed in the endothelium of the blood-brain barrier (BBB) and other abundant cell types within the brain. Mfsd2a transports DHA and other polyunsaturated fatty acids (PUFAs) esterified to lysophosphatidylcholine (LPC-DHA). However, the function of Mfsd2a and DHA in brain development is incompletely understood. Here, we demonstrate, using vascular endothelial-specific and inducible vascular endothelial-specific deletion of Mfsd2a in mice, that Mfsd2a is uniquely required postnatally at the BBB for normal brain growth and DHA accretion, with DHA deficiency preceding the onset of microcephaly. In Mfsd2a-deficient mouse models, a lipidomic signature was identified that is indicative of increased de novo lipogenesis of PUFAs. Gene expression profiling analysis of these DHA-deficient brains indicated that sterol regulatory-element binding protein (Srebp)-1 and Srebp-2 pathways were highly elevated. Mechanistically, LPC-DHA treatment of primary neural stem cells down-regulated Srebp processing and activation in a Mfsd2a-dependent fashion, resulting in profound effects on phospholipid membrane saturation. In addition, Srebp regulated the expression of Mfsd2a. These data identify LPC-DHA transported by Mfsd2a as a physiological regulator of membrane phospholipid saturation acting in a feedback loop on Srebp activity during brain development.